Constructing Latin America architecture, politics, and race at the Museum of Modern Art - Real, Patricio del (Yale University Press, 2022)
In the interwar period and immediately following World War II, the U.S. government promoted the vision of a modern, progressive, and democratic Latin America and worked to cast the region as a partner in the fight against fascism and communism. This effort was bolstered by the work and products of many institutions, including the Museum of Modern Art, New York. Using modern architecture to imagine a Latin America under postwar U.S. leadership, MoMA presented blockbuster shows, including Brazil Builds (1943) and Latin American Architecture since 1945 (1955), that deployed racially coded aesthetics and emphasized the confluence of "Americanness" and "modernity" in a globalizing world. Delving into the heated debates of the period and presenting never-before-published internal documents and photos from the museum and the Nelson A. Rockefeller archives, Patricio del Real is the first to fully address MoMA's role in U.S. cultural imperialism and its consequences through its exhibitions on Latin American art and architecture
Keywords: The Museum of Modern Art -- New York, NY; Geschichte 1930-1955; Geschichte 1943-1955; Kulturimperialismus; Ästhetik; Rassismus; Identität; Kunst; Ausstellung; Architektur; USA; Lateinamerika; Imperialism and architecture; Architecture / Latin America / Exhibitions; Architecture / Aspect politique / États-Unis; Museum of Modern Art (New York, N.Y.); Architecture; Architecture / Political aspects; Exhibitions / Political aspects; Latin America; United States; Exhibition catalogs